Mantle Modularity Underlies the Plasticity of the Molluscan Shell: Supporting Data From Cepaea nemoralis - Jackson, Daniel J. (Frontiers in Genetics, 2021)
Molluscs have evolved the capacity to fabricate a wide variety of shells over their 540+ million-year history. While modern sequencing and proteomic technologies continue to expand the catalog of molluscan shell-forming proteins, a complete functional understanding of how any mollusc constructs its shell remains an ambitious goal. This lack of understanding also constrains our understanding of how evolution has generated a plethora of molluscan shell morphologies. Taking advantage of a previous expression atlas for shell-forming genes in Lymnaea stagnalis, I have characterized the spatial expression patterns of seven shell-forming genes in the terrestrial gastropod Cepaea nemoralis, with the aim of comparing and contrasting their expression patterns between the two species. Four of these genes were selected from a previous proteomic screen of the C. nemoralis shell, two were targeted by bioinformatic criteria designed to identify likely shell-forming gene products, and the final one was a clear homolog of a peroxidase sequence in the L. stagnalis dataset. While the spatial expression patterns of all seven C. nemoralis genes could be recognized as falling into distinct zones within the mantle tissue similar to those established in L. stagnalis, some zones have apparently been modified. These similarities and differences hint at a modularity to the molluscan mantle that may provide a mechanistic explanation as to how evolution has efficiently generated a diversity of molluscan shells.